Collateral Regulation and IPO‐Specific Liberalisation: the Case of Price Limits in the Athens Stock Exchange. (22nd September 2014) - Thomadakis, Stavros; Gounopoulos, Dimitrios; Nounis, Christos; Merikas, Andreas
Abstract: This paper uses a unique testing ground on the effect of price limits upon IPO pricing and initial returns. The Athens Stock Exchange offers the opportunity for this new experiment, as three substantial changes in limit regulations were implemented in a short period of eight years. The results indicate significant differences in initial returns. Effective price limits reduce underpricing in all market segments, without visible diminution of IPO activity. The introduction of mandatory book‐building after price limits were phased out in Athens also led to reduced underpricing in the main market segment. Nevertheless, the existence of an independent effect of price limits explains why some regulators continue to use them to the present day.